Temporary VAT Reduction during the Lockdown - Evidence from Germany - Marius Clemens; Werner Röger (ZBW - Leibniz Information Centre for Economics, 2021)
This paper evaluates the temporary VAT reduction invoked by the German government over the third and fourth quarter of 2020 as part of the COVID-19 stimulus package. There is considerable controversy. Critics argue that VAT reductions are ineffective in the presence of lockdown measures in place and because of limited pass-through of temporary measures into consumer prices. Advocates emphasize positive effects on durables and stress that these measures can at least partly substitute for a limited monetary policy response under the ZLB. This paper sets up a DSGE model which is capable to address these issues. Our model distinguishes between sectors directly and indirectly affected by the lockdown. This allows us to trace economic spillovers of lockdown measures to the rest of the economy and the differentiated impact of VAT measures on the two sectors. We disaggregate consumption into durables and non-durables for both financially constrained and unconstrained households and we allow for imperfect pass-through of VAT measures into consumer prices, by noticing that the standard price setting model with convex cost of adjustment, makes strong predictions about magnitude and speed in which retailers are adjusting consumer prices to VAT shocks. We analyse the impact of the VAT in conjunction with the two lockdown shocks in 2020 Q2 to Q4. We use non-linear solution techniques to solve the model in the presence of a ZLB and a lockdown constraint and we carefully take into account the information set available for the private sector in each quarter on current and future policy measures. We find sizeable effects of VAT measures on consumption (esp. durables) with a multiplier larger than one on GDP and can match well the main macroeconomic aggregates over that period.
Keywords: E62; E65; H21; 330; Fiscal Policy; DSGE Modelling; COVID-19 Lockdown; Tax Multiplier